1994
DOI: 10.1095/biolreprod50.4.734
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Inhibin and Activin Binding Sites in the Testis during Development by in Situ Ligand Binding

Abstract: Inhibin and activin are related proteins thought to be potential paracrine regulators of testicular development and maintenance of spermatogenesis. Messenger RNA and proteins immunologically related to both factors have been identified in the adult testis. However, the role(s) of these factors in paracrine regulation of testicular function is poorly understood. To identify potential targets for inhibin and activin in immature and adult testis, we used in situ binding of [125I]-labeled ligands to localize and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…On the other hand, serum inhibin levels were low and were relatively constant in mature bulls tested in the present study. Thus, although recent evidence supports an autocrine or paracrine role for inhibin in regulating testicular function [12,13], inhibin does not seem to be directly involved in the improvement of the quantity and quality of semen. In summary, the present study showed agerelated changes in serum concentrations of inhibin, gonadotropins and testosterone.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, serum inhibin levels were low and were relatively constant in mature bulls tested in the present study. Thus, although recent evidence supports an autocrine or paracrine role for inhibin in regulating testicular function [12,13], inhibin does not seem to be directly involved in the improvement of the quantity and quality of semen. In summary, the present study showed agerelated changes in serum concentrations of inhibin, gonadotropins and testosterone.…”
Section: Discussionmentioning
confidence: 92%
“…In testis, it is reported that inhibin produced in Sertoli cells affects spermatogonial proliferation [9,30] and is related to the modulation of LH-stimulated androgen biosynthesis [3,27,33]. In fact, inhibin was taken up by spermatocytes in human testis [31], and inhibin-binding sites are localized in rat Leydig cells [13]. These reports suggest that inhibin produced in Leydig cells might play a paracrine/autocrine role in the regulation of androgen production.…”
Section: Discussionmentioning
confidence: 97%
“…Delineation of an intracellular signalling pathway for inhibin awaits unequivocal proof of a receptor for inhibin, about which controversy regarding its very existence persists. The evidence presented supporting the existence of an inhibin receptor is based on the identification of specific binding sites for inhibin on ovarian granulosa cells and Leydig cells (Woodruff et al 1990, Krummen et al 1994. Additional supporting data for the existence of a specific receptor include the demonstration of an inhibin-specific protein complex, k562, in haematopoietic cell lines (Lebrun & Vale 1997) and tumour-derived inhibin receptor proteins in the Matzuk inhibin knockout mice (Draper et al 1998).…”
Section: Inhibin and Activin Receptors And Signallingmentioning
confidence: 99%